Use of Electronic Medical Record Data for Quality Improvement in Schizophrenia Treatment - Owen, Richard R. (American Medical Informatics Association, 2004)
An understanding of the strengths and limitations of automated data is valuable when using administrative or clinical databases to monitor and improve the quality of health care. This study discusses the feasibility and validity of using data electronically extracted from the Veterans Health Administration (VHA) computer database (VistA) to monitor guideline performance for inpatient and outpatient treatment of schizophrenia. The authors also discuss preliminary results and their experience in applying these methods to monitor antipsychotic prescribing using the South Central VA Healthcare Network (SCVAHCN) Data Warehouse as a tool for quality improvement.